find g(x+3) given g(x)=5x-1

2 answers

g(x) = 5x - 1

Let's take y = x + 3

Now, g(y) = 5y - 1

So, g(x + 3) = 5y - 1
But y = (x + 3)
=> g(x + 3) = 5(x + 3) - 1
= 5x + 15 - 1
= 5x + 14
Given: g(x) = 5x-1.
Find: g(x+3).

In the given Eq, replace x with (x+3):
g(x+3) = 5(x+3) - 1.
g(x+3) = 5x + 14.
Similar Questions
  1. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 1 answer
  2. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 0 answers
  3. Let equation of an hyperbola be y^2-4x^2+4y+24x-41=0a. Find the standard form b. Find the center c. Find the vertices d. Find
    1. answers icon 0 answers
  4. For the following graph:a. Find the domain of f. b. Find the range of f. c. Find the x-intercepts. d. Find the y-intercept. e.
    1. answers icon 1 answer
more similar questions